The effects of local over-expression of VEGF on the uterine arteries and uterine artery endothelial cells of pregnant sheep. (16th November 2010) - Mehta, V; Abi-Nader, K; Buitendyk, M; Torondel, B; Shaw, SW; Boyd, M; Benjamin, E; Zachary, IC; Martin, JF; Peebles, DM; David, AL
Abstract : Introduction: Impaired utero-placental perfusion leads to fetal growth restriction. The authors have shown a significant increase in blood flow in the uterine arteries (UAs) of pregnant sheep and a significantly reduced contractile response following local transduction with an adenovirus encoding VEGF-A165 (Ad.VEGF-A). The authors have now studied the effects of local over-expression of the VEGF-D ΔNΔC isoform and investigated the mechanism behind the VEGF (−A and −D ΔNΔC ) induced effects. Method: UAs of mid-gestation pregnant sheep were injected with adenovirus vectors (5×10 11 particles) encoding the VEGF-D ΔNΔC gene (Ad.VEGF-D) and a reporter β-galactosidase gene (Ad.LacZ) contra-laterally. Sheep were killed 4–7 days later. UAs were isolated and their vasoreactivity studied on an organ bath. Adventitial blood vessels were enumerated by anti-vWF immunohistochemistry. Endothelial cells (ECs) were isolated from the UAs of control mid-gestation pregnant sheep, cultured and infected with Ad.VEGF-A vector. Protein was extracted from these uterine artery endothelial cells (UAECs) infected ex vivo and assayed for endothelial nitric oxide synthase (eNOS) levels by Western blotting. Results: There was a significant reduction in the UA contractile response following Ad.VEGF-D when compared to Ad.LacZ transduction (Emax 126.6±7.54 vs 159.9±10.96, p<0.001, n=5) and vasorelaxation was enhanced (pD2 (−log EC50 ) 9.05±0.14 vs 8.87±0.16, p=0.55, n=4). eNOS levels increased with rising adenovirus vector concentrations in UAECs transduced ex vivo. There were significantly higher numbers of blood vessels in the perivascular adventitia of Ad.VEGF-D transduced vessels compared to Ad.LacZ transduced vessels (140.6±15.1 vs 91.7±9.9, p<0.05). Conclusion: Changes in eNOS levels and vascular remodeling may be the underlying mechanism of action of local VEGF over-expression in pregnant sheep UAs.